Colour difference evaluation using display colours. (December 2018) - Liang, J; Georgoula, M; Zou, N; Cui, G; Luo, M Ronnier
Two separate but similar experiments were carried out at Leeds University (UK) and Zhejiang University (China), respectively. Both experiments were conducted to assess colour differences using Eizo displays using the ratio method. Eleven of the MacAdam centres within the colour gamut of the display were studied. Each centre included 21 samples assessed against a grey and a black background. The reason for using these different backgrounds was to simulate viewing a surface colour (surface mode) and a light source in the dark (illuminant mode), respectively. The results revealed that there were parametric effects for different backgrounds and luminances. The data were better fitted by CIELAB and CIELUV for the illuminant mode while CAM02-UCS performed best for the surface mode. The patterns of the ellipses between the data collected in these experiments and the original MacAdam data, show systematic discrepancies.